(untitled) (Journal of School Administration Research and Development, 2016)
School leadership has been a burgeoning topic in education since the turn of the millennium. There is no shortage of research, articles with best practices, and “how to” books on educational leadership. Unfortunately, the development and selection of school leaders has only recently started to gain the attention of educational stakeholders. Initiatives such as the Wallace Foundation’s Principal Pipeline Initiative, which started several years ago, has focused attention on the development of school leaders, while the selection of school leaders is still emerging as a topic of interest.